MicroRNAs as regulators of drug abuse and immunity - Kai Zhang; Xuxiu Jing; Guoqiang Wang (Central European Journal of Immunology)
MicroRNAs (miRNAs) are 20-22 nucleotide non-coding RNAs that participate in gene regulation. They bind to 3’-untranslated regions of their mRNA targets, inhibiting the transcripts’ translation and/or destabilizing them. Chronic drug abuse induces changes of miRNAs expression in the brain, which is thought to contribute to addictive behaviors. Lots of miRNAs have been identified to play critical roles in the development of drug addiction. Moreover, miRNAs have been shown to play critical roles in a broad array of biologic processes, including regulation of the cell cycle, oncogenic transformation, immune cell regeneration and differentiation, and psychiatry disorders. We hypothesized that chronic drug abuse leads to aberrant expression of several miRNAs, and then aberrant miRNAs influence the innate and adaptive immunity, especially differentiation and function of T cells and B cells, through down-regulated miRNAs’ target gene expression. Characterization of miRNA actions is important and has high potential effect for the management of drug addiction and immunity diseases. miRNAs are potential biomarkers, and the modulation of their expression can be used for therapeutic purposes.